Pengaruh Green Accounting dan Kinerja Lingkungan terhadap Sustainable Development Goals pada Perusahaan Manufaktur Sektor Barang Konsumsi Tahun 2021-2023 - Rahmatika; Nadia, Putri; Yupita, Lasmi (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
Global challenges in dealing with hunger, poverty, social inequality, environmental pollution, climate change, and several other important issues encourage the creation of the concept of sustainable development goals. This quantitative method research was conducted to determine the impact of green accounting implementation and environmental performance on sustainable development goals. The criteria selection process resulted in 33 samples from manufacturing companies in the consumer goods sector that published complete annual reports and sustainability reports in 2021-2023. The company also received a PROPER certificate for three consecutive years as a form of commitment to preserving the environment. This study uses multiple linear regression analysis and a series of tests, namely the classical assumption test, the coefficient of determination test, and the hypothesis test. The t-test results reveal that green accounting is unable to influence sustainable development goals. Some companies are still not transparent in conveying information about environmental costs in annual reports and sustainability reports. Furthermore, the t-test results state that environmental performance is able to influence sustainable development goals. This is evidenced by the acquisition of a consistent company environmental performance rating every year.